PENATAAN, PEMELIHARAAN DAN PELAYANAN ARSIP DINAMIS INAKTIF DI KANTOR PERTANAHAN KABUPATEN BANTUL - , SINDU LAKSONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The title of this final report is âThe Arrangement, Keeping and Service Of Inactive Records In Bantul Kantor Pertanahan Kabupaten Bantulâ. This report was prepared after finishing for two months the job training. The purpose of writing this final report is to determine the arrangement of a system of records maintained in Record Center in Kantor Pertanahan Kabupaten Bantul. Arrangement of inactive records in Kantor Pertanahan Kabupaten Bantul consists of sorting stage archive types, grouping or maneuver, binding and labeling that uses multiple filing systems, keeping and preservation of the records can be used until the user records in the service of lending and recovery of records. Collection methods used in the preparation of this final report is to study literature by using reference materials relevant to the title, observation and participation by observing the activities office to participate directly in Kantor Pertanahan Kabupaten Bantul, and then interviews with record officer to obtain accurate information in the arrangement, keeping and service of inactive records in Kantor Pertanahan Kabupaten Bantul. In conclusion, the arrangement, keeping and service of inactive records in Kantor Pertanahan Kabupaten Bantul has not performed optimally. Archival procedures have not been implemented seriously, such as lack of infrastructure, ineffective service, ineffective keeping and security archives. It happens because it does not have archivists in Kantor Pertanahan Kabupaten Bantul.